Goethe yearbook. - Krimmer, Elisabeth; Daub, Adrian; Franzel, Sean (Goethe Yearbook, 2017)
The Goethe Yearbook is a publication of the Goethe Society of North America, encouraging North American Goethe scholarship by publishing original English-language contributions to the understanding of Goethe and other authors of the Goethezeit while also welcoming contributions from scholars around the world. Volume 24 features a special section titled "The Poetics of Space in the Goethezeit," co-edited by John Lyon and Elliott Schreiber, with contributions on blind spots in Goethe's Elective Affinities; on the topography and topoi of Goethe's autobiographical childhood; on disorientation and the subterranean in Novalis; on selfhood, sovereignty, and public space in Die italienische Reise and Dichtung und Wahrheit; on Goethe's theater of anamnesis in Wilhelm Meisters Lehrjahre; and on spatial mobilization in Kleist's Berliner Abendblätter. There are also articles on the horror of coming home in Caroline de la Motte Fouqué's "Der Abtrünnige" and on Friedrich Heinrich Jacobi's Eduard Allwills Papiere. Contributors: Colin Benert, Stephanie Galasso, Tove Holmes, Edgar Landgraf, Sara Luly, John B. Lyon, Anthony Mahler, Monika Nenon, Joseph O'Neil, Elliott Schreiber, Inge Stephan, Gabriel Trop, Christian P. Weber Adrian Daub is Associate Professor of German at Stanford. Elisabeth Krimmer is Professor of German at the University of California Davis. Book review editor Birgit Tautz is Associate Professor of German at Bowdoin College.